Accelerated high fluence photoactivated chromophore for infectious keratitis—corneal cross-linking (PACK-CXL) at the slit lamp: a pilot study - Olshaker, Hagar; Achiron, Asaf; Chorny, Alexander; Hafezi, Farhad; Yahalomi, Tal; Kratz, Assaf; Tsumi, Erez; Lu, Nan-Ji; Knyazer, Boris (Frontiers in Pharmacology, 2023)
Introduction: Photoactivated Chromophore for Infectious Keratitis-Corneal Cross-Linking (PACK-CXL) has garnered substantial interest among researchers and ophthalmologists due to its high promise as a potential treatment for infectious keratitis. The aim of this study is to evaluate the efficacy and safety of high fluence PACK-CXL, using 10.0 J/cm² (30 mW/cm², 5 minutes and 33 seconds) at the slit lamp. Methods: This prospective interventional, nonrandomized cohort study included 20 eyes of 20 patients with bacterial, fungal, or mixed origin keratitis who underwent high fluence PACK-CXL treatment as an adjunct therapy to conventional antimicrobial therapy per American Academy of Ophthalmology treatment guidelines. The re-epithelization time was recorded, and corneal endothelial cell density was counted before and after treatment. Results: The average re-epithelization time was 8.2 ± 2.8 days (range 3-14 days). After PACK-CXL treatment, eight patients (40%) were directly discharged, while the remained patients stayed in the hospital for an average of 5.6 ± 3.5 days. No eyes required keratoplasty. Endothelial cell density counts before and after the PACK-CXL procedure were 2562.1 ± 397.3 and 2564.8 ± 404.5 cells/mm2, respectively (P = 0.96). Conclusion: although it wasn’t a randomized control trial, we conclude that high fluence PACK-CXL as an adjuvant therapy is safe with no complications observed, and efficient as time to re-epithelization was less than 14 days for all patients and no patients underwent tectonic keratoplasties. Further research is needed to compare it to the current standard of care.